Investment in financial literacy and saving decisions - Jappelli, Tullio; Padula, Mario (Journal of Banking & Finance, 2013)
We present an intertemporal consumption model of investment in financial literacy. Consumers benefit from such investment because financial literacy allows them to increase the returns on wealth. Since literacy depreciates over time and has a cost in terms of current consumption, the model delivers an optimal investment in literacy. Furthermore, literacy and wealth are determined jointly, and are positively correlated over the life-cycle. The model drives our empirical approach to the analysis of the effect of financial literacy on wealth and saving and indicates that the stock of financial literacy early in life is a valid instrument in the regression of wealth on financial literacy. Using microeconomic and aggregate data, we find strong support for the model’s predictions.